Eksplorasi dan Karakterisasi Varietas Mangga Tahan Hama Penggerek Batang di Nanggroe Aceh Darussalam - Siti Hafsah; Jauharlina Jauharlina; Tjut Chamzurni (Fakultas Pertanian, Universitas Syiah Kuala, 2010)
Exploration and Characterization of Mango Variety Resist of Cork bore in Nanggroe Aceh DarussalamABSTRACT. The basic knowledge about mango resistance of trunk bore in the field and laboratory is early step to make mango resistance breeding. The result of research could be positive correlation between resistance character and commercial character. The research consisted two parts, survey of varieties of mango on field and the resistance test of trunk borer of mango on laboratory. The survey was done by characterization of mango varieties on Aceh Besar and Banda Aceh. The laboratory research was held by varieties of mango (Arumanis, Gadung, Golek, Cengkeh, Apel and Local) the test of resistance of trunk borer of mango. All treatment was assigned in Completely Randomized Design with 3 replications. The observation was done on characterization of mango varieties, percent of damage, damage index, insect identification and soluble solids contents. This result showed that there are six varieties of mango (Arumanis, Cengkeh, Gadung, Apel, Golek and Local (cengkir) has be found on Banda Aceh and Aceh Besar. Percent damage of trunk borer of mango on Aceh Besar (50-100%) and intensity of damage (10-60%). Percent damage (0-100%) and intensity of damage (0-30%) on Banda Aceh is Lower than Aceh Besar. The soluble solid contents of mature fruit of Golek, Gadung, Cengkeh and Arumanis 13.90-15.68 0brix) higher than Apel and Local (11.54 and 12.72 0brix). Result of identification of insect that trunk borer og mangoes on Banda Aceh and Aceh Besar is Rhytidodera simulans Wh.